2010
DOI: 10.2147/vhrm.s4619
|View full text |Cite
|
Sign up to set email alerts
|

Managing anemia in patients with chronic heart failure: what do we know?

Abstract: Anemia is common in patients with chronic heart failure (HF) with an incidence ranging from 4% to 55% depending on the studied population. Several studies have highlighted that the prevalence of anemia increases with worsening heart failure as reflected by New York Heart Association classification. Additionally, several epidemiological studies have highlighted its role as a prognostic marker, linking it to worse outcomes including; malnutrition, increased hospitalizations, refractory heart failure and death. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 101 publications
1
7
0
Order By: Relevance
“…In our study, anaemia was frequently observed, found in over one-third of HF patients. This is similar to previously observed frequencies [ 1 - 4 ] emphasising that a large part of the patient population with HF has anaemia as a possible factor of co-morbidity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, anaemia was frequently observed, found in over one-third of HF patients. This is similar to previously observed frequencies [ 1 - 4 ] emphasising that a large part of the patient population with HF has anaemia as a possible factor of co-morbidity.…”
Section: Discussionsupporting
confidence: 91%
“…Anaemia is common in patients with heart failure (HF) and is found in 4%-55% of the patients [ 1 - 4 ]. Many studies have demonstrated anaemia to be a risk factor in patients with heart failure [ 5 , 6 ] and anaemia is currently targeted in several interventional trials.…”
Section: Introductionmentioning
confidence: 99%
“…69 HF is known to cause a sustained increase in the concentration of serum proinflammatory cytokines, including IL-1, IL-6, IL-18, and TNF-␣, which can lead to an increase in platelet count. 70,71 The study patients also had normal RBC counts, hemoglobin, or packed cell volumes, thus eliminating anemia as a cause for hyperlactatemia. 43 The limitations of this study include the lack of treatment standardization because the therapeutic approaches had to meet the clinical needs of each patient.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, anemic patients with CHF have more commonly diabetes mellitus and more advance disease, with higher NYHA class and more severe symptoms. Those symptoms include lower exercise capacity, worse quality-of-life scores, greater peripheral edema, lower dry weight and blood pressure, higher use of diuretics and other cardiovascular medications, and worse neurohormonal profile (such as renal dysfunction, high BNP and C-reactive protein, low serum albumin) (range, 30% to 61% versus range, 4% to 23% for less symptomatic ambulatory patients) [ 23 , 24 ]. It is remarkable that anemia does not seem to be related to LV dysfunction, whereas in few studies Hb levels were inversely related to EF.…”
Section: Epidemiology Of Anemia In Heart Failurementioning
confidence: 99%
“…Finally, most studies indicate that the prevalence of anemia is increased in patients with CHF who also have co-morbid kidney disease, advanced age, and more severe symptoms when compared to less symptomatic ambulatory populations [ 23 ].…”
Section: Epidemiology Of Anemia In Heart Failurementioning
confidence: 99%